2021
DOI: 10.3126/janr.v4i2.33857
|View full text |Cite
|
Sign up to set email alerts
|

Technical efficiency of wheat growing farmers of Nepal

Abstract: Wheat is a major staple food crop of Nepal, so it is necessary to increase its productivity. However, the national average wheat productivity of Nepal is low as compared to other neighboring countries. This study employed a Cobb-Douglas stochastic production frontier model to examine the technical efficiency and its determinants using randomly selected household data from 343 wheat farmers from four districts of Nepal. Maximum likelihood estimation results showed that wheat production responded positively to a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 13 publications
0
1
0
Order By: Relevance
“…This applies that technical efficiency of maize farmers in the study area could be increased by 18.53 %. Majority (41%) of farmers are producing technically efficient maize output, however they can still improve their productivity by 18% to realize the full potential of maize production in the study area [11][12][13][14][15].…”
Section: Resultsmentioning
confidence: 99%
“…This applies that technical efficiency of maize farmers in the study area could be increased by 18.53 %. Majority (41%) of farmers are producing technically efficient maize output, however they can still improve their productivity by 18% to realize the full potential of maize production in the study area [11][12][13][14][15].…”
Section: Resultsmentioning
confidence: 99%
“…This is in line with the findings by Okello et al (2019) who found out that farmers in Gulu had higher allocative efficiency than their counterparts in Amuru district. Additionally, Adhikari et al (2021) and Tsoho et al (2012) also found out that farm location had a significant association with technical, allocative and economic efficiency among different crops. Accordingly, the results (Table 6) showed that farmers belonging to agricultural groups had 10.16% higher technical efficiency than their fellows who did not belong to the groups.…”
Section: Determinants Of Technical Efficiencymentioning
confidence: 91%
“…The escalating demand for food at an unprecedented rate emphasizes the importance of timely information on crop growth stages and maturity for effective decision-making, emergency response mechanisms, and efficient monitoring of food production [3]. As a result, various approaches have been employed to model crop yield, including field surveys, expert assessments, farm reports, and forecasting models [4][5][6]. In recent years, integrating remote sensing and machine learning tools has sparked a fundamental shift in sustainable agriculture.…”
Section: Introductionmentioning
confidence: 99%